Traditional Methods in Arabic Language Instruction: A Critical Review of Classical Pedagogies - Dadan Mardani; Isop Syafei (International Journal of Islamic Educational Research, 2025)
This article examines the foundational role of traditional methods in Arabic language instruction by exploring classical pedagogies rooted in Islamic educational heritage. Amid the rising dominance of modern and communicative approaches, a critical reassessment of historical methods—such as imlāʾ, talqīn, qirāʾah jahrīyah, ḥifẓ, and tarjamah—is necessary to understand their pedagogical strengths, limitations, and philosophical underpinnings. This study employs a reflective literature-based method that draws upon classical Islamic texts, modern comparative analyses, and recent academic contributions to reconstruct the theoretical framework of traditional instruction. Findings reveal that while classical methods emphasized memorization, authority, and textual mastery, they also embodied a coherent epistemology centered on ethical formation (adab), teacher–student transmission (taqlīd), and spiritual-intellectual integration. These methods were not only instructional techniques but were embedded within broader ontological and axiological assumptions about knowledge, language, and human development. The study argues that rather than being entirely outdated, elements of traditional pedagogy remain relevant and can be selectively integrated into modern educational models to balance structure with creativity, discipline with dialogue. By critically reviewing classical pedagogies, this article contributes to the discourse on Arabic language curriculum reform, especially in Islamic institutions seeking to preserve identity while engaging contemporary educational challenges